Pengaruh Pendidikan Kesehatan dengan Media Video terhadap Kepatuhan Diit Hipertensi pada Lansia di Puskesmas Purwokerto Timur 2 - Agun Pangestu; Wasis Eko Kurniawan; Tri Sumarni (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Elderly is the final phase of the human journey where there will be changes and decline in organ function due to the aging process. The incidence of hypertension in the elderly is seen to increase from 2013 to 2018 reaching 25.8% and increasing to 34.1% in 2018. Hypertension diet is one of the non-pharmacological therapies to control and maintain normal blood pressure values. Health education is an activity to convey health messages to individuals, groups or communities that aims to improve health using video media. The purpose of this study was to analyze the effect of health education with video media on adherence to hypertension diet in the elderly at Pukesmas Purwokerto Timur 2. This study was a quantitative study with a pre-experimental design one group pre and post test using accidental sampling technique with a total sample of 30 elderly respondents. and using a questionnaire instrument Formular Food Frequency Questionnaire. Analysis using univariate test, bivariate and Wilcoxon test. The results of the Wilcoxon statistical test show that there is an influence between health education and video media on hypertension diet compliance with a p-value of 0.000, so that there is a decrease in the number of daily calories by 141.1 Kcal (5.71%), after being given a video, the average number of calories in the elderly before being given a video was 2470.07 kkl, after being given a video the average was 2328,97 kkl.